Răspuns :
a + b + c = 695
a - b = 256 => b = a - 256
a - c = 192 => c = a - 192
a + a - 256 + a - 192 = 695
3a = 695 + 448
a = 1143 : 3
a = 381
b = 381 - 256
b = 125
c = 381 - 192
c = 189
a - b = 256 => b = a - 256
a - c = 192 => c = a - 192
a + a - 256 + a - 192 = 695
3a = 695 + 448
a = 1143 : 3
a = 381
b = 381 - 256
b = 125
c = 381 - 192
c = 189
|--------|256|
|--------|
|--------|64|
695 - (256+64) =
695 - 320 = 375
375:3 = 125 b
125+256 = 381 (a)
125+64 = 189 (c)
|--------|
|--------|64|
695 - (256+64) =
695 - 320 = 375
375:3 = 125 b
125+256 = 381 (a)
125+64 = 189 (c)